Leptin Promotes the Myofibroblastic Phenotype in Hepatic Stellate Cells by Activating the Hedgehog Pathway - Choi, Steve S. (American Society for Biochemistry and Molecular Biology, 2010)
Trans-differentiation of quiescent hepatic stellate cells (Q-HSCs), which exhibit epithelial and adipocytic features, into myofibroblastic-HSC (MF-HSCs) is a key event in liver fibrosis. Culture models demonstrated that Hedgehog (Hh) pathway activation is required for transition of epithelioid/adipocytic Q-HSCs into MF-HSCs. Hh signaling inhibits adiposity and promotes epithelial-to-mesenchymal transitions (EMTs). Leptin (anti-adipogenic, pro-EMT factor) promotes HSC trans-differentiation and liver fibrosis, suggesting that the pathways may interact to modulate cell fate. This study aimed to determine whether leptin activates Hh signaling and whether this is required for the fibrogenic effects of leptin. Cultures of primary HSCs from lean and fa/fa rats with an inherited ObRb defect were examined. Inhibitors of PI3K/Akt, JAK/STAT, and Hh signaling were used to delineate how ObRb activation influenced Hh signaling and HSC trans-differentiation. Fibrogenesis was compared in wild type and db/db mice (impaired ObRb function) to assess the profibrotic role of leptin. The results demonstrate that leptin-ObR interactions activate Hh signaling with the latter necessary to promote trans-differentiation. Leptin-related increases in Hh signaling required ObR induction of PI3K/Akt, which was sufficient for leptin to repress the epithelioid/adipocytic program. Leptin-mediated induction of JAK/STAT was required for mesenchymal gene expression. Leptin-ObRb interactions were not necessary for HSC trans-differentiation to occur in vitro or in vivo but are important because liver fibrogenesis was attenuated in db/db mice. These findings reveal that leptin activates Hh signaling to alter gene expression programs that control cell fate and have important implications for liver fibrosis and other leptin-regulated processes involving EMTs, including development, obesity, and cancer metastasis.